PENGARUH LINGKUNGAN KERJA, KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA KEPALA SEKOLAH DASAR NEGERI KECAMATAN KRAMAT JATI JAKARTA TIMUR - HANIFAH, NANI (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
The objective of this research is to study the effects of work environment, leadership and work motivation on the performance of state elementary school principals in Kramat Jati the subdistrict of East Jakarta. The research was conducted by survey method with path analysis. The sample size was 59 principals of state elementary schools, by using the simple random sampling technicque.The results of the research are as follows: (1) there is a direct effect of the work environment toward work motivation; (2) there is a direct effect of leadership on work motivation; (3) there is a direct effect of the work environment on the performance of the principals; (4) there is aÂ direct effect of the leadership on performance of the principals; (5) there is aÂ direct effect of the work motivation on performance principals. Based on the findings of this research that the performance of state elementary school prinscipals in Kramat Jati the subdistrict of East Jakarta was significantly influenced by work environment, leadership and work motivation. It could be concluded that enhanching performance of principals would be determined by increasing the work environment, leadership and work motivation.Keywords: work environment,Â leadership,Â motivation,Â school-principalâs performance